2014
DOI: 10.1515/hf-2014-0148
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and ultrastructural changes of ash wood thermally modified using the thermo-vacuum process: I. Histo/cytochemical studies on changes in the structure and lignin chemistry

Abstract: Changes in structure and lignin chemistry were investigated in ash wood thermally modified (TMW) by the thermo-vacuum (Termovuoto) process for 3 h at 190–220°C by means of light, fluorescence, and transmission electron (TEM) microscopy combined with histo/cytochemistry. Variation in changes in native cell color in TMWs was positively correlated with differences in lignin content between cell types and cell wall regions in the reference wood. Histochemical staining showed increasing amounts of acidic groups in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Lignin fluorescence is sensitive to the molecular environment and so can be manipulated with pH and by treatment with quenching agents such as nitrophenol-labeled carbohydrates [32,41]. Heat treatment [41,42] and infiltration with modifying chemicals [43] can also influence lignin autofluorescence. Lignin fluorescence can, therefore, be used as a biosensor for various research investigations such as measurement of cell wall porosity or detection of infiltrating chemicals in wood modification studies.…”
Section: Ligninmentioning
confidence: 99%
“…Lignin fluorescence is sensitive to the molecular environment and so can be manipulated with pH and by treatment with quenching agents such as nitrophenol-labeled carbohydrates [32,41]. Heat treatment [41,42] and infiltration with modifying chemicals [43] can also influence lignin autofluorescence. Lignin fluorescence can, therefore, be used as a biosensor for various research investigations such as measurement of cell wall porosity or detection of infiltrating chemicals in wood modification studies.…”
Section: Ligninmentioning
confidence: 99%
“…Detailed analyses of individual TW regions and bres after staining was conducted using a Leica DMLB light microscope (Leica Microsystems, Wetzlar, Germany) equipped with an In nity X-32 digital camera (Deltapix, Samourn, Denmark) to con rm presence/absence of TW and G-layers. To visualize lignin distributions, fresh sections were stained using the Wiesner and Mäule reactions [47,48]. For the Wiesner reaction, sections were treated with 2 % v/v phloroglucinol in ethanol and mounted in 6 M hydrochloric acid.…”
Section: Sectioning and Staining Of Stem Cross-sections For Tension Woodmentioning
confidence: 99%
“…Our previous histochemical study of ash wood showed overall stronger lignin staining by Wiesner reaction (i.e. total lignin) in ray/axial parenchyma cells than fibers which were more like vessels (Kim et al, 2014). However, there is also a possibility of an effect of syringyl (S) lignin on resistance of ray/axial parenchyma cells since unlike softwoods, lignin in hardwood xylem cells is composed of both G and S lignin (Donaldson, 2001).…”
Section: Decay Of Parenchyma Cell Wallsmentioning
confidence: 98%
“…The S/G ratio also varies between cell types in hardwoods (Donaldson, 2001). In addition, ash wood also showed high variation in S/G ratio depending on cell type and location within a growth ring (Kim et al, 2014). Schwarze (2007) proposed that the cell wall morphology rather than lignin composition and amount may be responsible for higher resistance of parenchyma cells than fibers.…”
Section: Decay Of Parenchyma Cell Wallsmentioning
confidence: 99%